ĐỘNG VẬT HOANG DÃ VỚI CHIẾN LƯỢC PHÁT TRIỂN BỀN VỮNG Ở VIỆT NAM - Huỳnh, Đặng Huy (Nhà xuất bản Nông nghiệp, 2016)
Viet Nam has a rich diversity of mammals and bird, reptile, amphibian, fish and many of them are regional or national endemic species. Many species of fauna are important to sustainable development of the country. Before the 1970s, forest types were diverse with abundance of wild animals such as elephant, rhino, tiger, wild cows and buffaloes, reptiles and so on. But now it’s difficult to observe them in natural reserves, even in national parks. Unsustainable use of zoo resources is one of the main reason of wildlife loss. This paper presents the author’s proposals for wildlife conservation measures. They includes: (1) continuity for surveys and inventories to have an accurate assessment of zoo diversity in all the nature reserves; (2) establishment of strict conservation habitats areas; (3) organizing search for rare and endangered species; (4) limit and end legal trade of endangered species; (5) practicing settlement cultivation policy; (6) supporting buffer zones - especially where the minority people stay; and (7) establishing international cooperation with the neighboring countries, including Laos, Cambodia, Thailand, and China.